Implementasi Multi-Stakeholder Partnership dalam Penguatan Pelayanan Pusat Kesejahteraan Sosial di Desa Cibadak - Bernyssa Asti Kirana; Rizki Aditya Putra; Devita Damayanti; Gresia Dwi Cahyani Hutauruk; Shafira Rizkyanty; Tri Amanda Putri Harahap; Iman Kasiman Nawireja (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2025)
The Social Welfare Center (PUSKESOS) of Cibadak Village, Bogor is an organization established in 2023 by the Social Service with the involvement of Cibadak Village in selecting officers to carry out services for the community. High enthusiasm of the community towards the presence of PUSKESOS has resulted in an imbalance between service times and community demand for the number of workers. Institutional strengthening is needed by PUSKESOS in facing challenges and forming development strategies through a Multi-Stakeholder Partnership approach. This research aims to examine the influence of PUSKESOS collaboration with various partners using the Multi-Stakeholder Partnership theory to evaluate the impact of partnerships on services along with supporting and inhibiting factors in the running of the PUSKESOS organization in Cibadak Village. The method used in this research is a qualitative approach with data collection techniques in the form of interviews as a primary data collection tool. The research results show that PUSKESOS has succeeded in building collaborative involvement between stakeholders with service development strategies implemented to maximize PUSKESOS services including service improvements in data input training and the use of technological facilities as well as monitoring and evaluation activities to facilitate the service process for the people of Cibadak Village.